Effects of Four Sulfonate-Containing Additives and Hydroxyethyl Cellulose on the Properties of Electrolytic Copper Foils - Wei Wang; Jun Tao; Kaiwen Tong; Zhiqiang Xu; Fuqi Zhong; Jianping Dong; Yanxia Chen; Zhengbing Fu; Caiqin Qin (Molecules)
Ultrathin electrolytic copper foils with a thickness of 6 μm were prepared by a test machine using copper sulfate electrolyte with gelatin, hydroxyethyl cellulose (HEC), and sulfonic acid-containing organics as additives. The effects of four sulfonic acid-containing organic additives, sodium 3-mercaptopropanesulfonate (MPS), bis-(sodium sulfopropyl)-disulfide (SPS), sodium 3-[[(dimethylamino)thioxomethyl]thio]propanesulfonate (DPS), and sodium 3-((4,5-dihydrothiazol-2-yl)thio)propane-1-sulfonate (TPS), on the physical property of copper foils were investigated. The results show that all these additives can effectively improve the gloss and tensile strength of electrolytic copper foil, and the texture coefficients of Cu(111) selectivity increase. The synergistic use of HEC and TPS can effectively reduce the pinholes of copper foil.